DIGESTIVE POTENTIAL CHARACTERISTICS AND LACTOTROPHYC ADEQUACY PREDICTION BASED ON THE STUDY OF NEWBORNS’ GASTRIC ASPIRATE HYDROLASES - G. Y. MODEL; I. M. BYKOV; G. A. PENZHOYAN; E. E. BRESHCHENKO (Кубанский научный медицинский вестник, 2017)
Aim. To study the hydrolases of the gastric aspirate of newborns and to estimate the digestive potential of their digestive systems at full-term and preterm gestational age.Materials and methods. Samples received from 76 full-term (37-41 weeks of gestation) and preterm (27-36 weeks) neonates have been studied in the course of this research. Lipase, α-amilase, the alkaline phosphatase, α-1- antitrypsin, pepsinogens I and II have been found in the supernatant of aspirate of the gastric content taken on an empty stomach.Results. The results of the study indicate the significant decrease in the hydrolase content in the gastric aspirate of preterm infants in comparison with full-term infants as well as the decrease in the initial digestive potential at the preterm gestational age. These results update the digestive potential definition din labor as the diagnostic one in the trophological prediction of newborns development. Concluson. The initial digestive potential of the digestive system of a newborn is characterized by hydrolase contents in his/her gastric aspirate. At the preterm gestational age the digestive potential of the digestive system is variously decreased for different hydrolase systems. The estimation of the initial digestive potential of newborns is promising for choosing strategies in breast, mixed and bottle feeding.